The relationship between oxidative stress markers and 1H-Magnetic resonance spectroscopy findings in obsessive compulsive disorder - Turgut, Fatma Subasi; Bulut, Mahmut; Hattapoglu, Salih; Gunes, Mehmet; Kaya, Mehmet Cemal; Ekici, Faysal; Atmaca, Murad (Elsevier, 2024)
Introduction: The purpose of this study was to examine N-acetyl aspartate (NAA)/creatine (Cr) and glutamate, glutamine, and gamma-aminobutyric acid complex (Glx)/Cr levels in patients with obsessive compulsive disorder (OCD) and healthy controls' orbitofrontal cortex (OFC) and caudate nucleus (CN) by proton magnetic resonance spectroscopy (1H-MRS) method and to investigate their relationship with oxidative stress markers glutathione peroxidase (GPx) and superoxide dismutase (SOD). Methods: This study included patients with OCD (n = 25) and healthy controls (n = 25) ranging in age from 18 to 65. We used the ELISA method to evaluate serum SOD and GPx levels. Levels of NAA/Cr and Glx/Cr in the orbitofrontal cortex and caudate nucleus were measured using the 1H-MRS method. Results: Our study did not detect statistically significant differences in the orbitofrontal cortex Glx/Cr and NAA/ Cr levels between the OCD patients and the control group. OCD patients exhibited a decrease in NAA/Cr levels, consistent with impaired neuronal integration, and an increase in Glx/Cr levels, consistent with hyperactivation, in the caudate nucleus compared to the control group. We observed a negative correlation between NAA/Cr levels in the caudate nucleus and the levels of SOD and GPx. Conclusions: Our study is the first to assess CN and OFC together in OCD patients using 3 T MR, investigating the relationship between neurometabolite concentrations and oxidative stress parameters. The negative correlation we observed between NAA/Cr levels and SOD and GPx in the caudate nucleus suggests that increased oxidative stress in this brain region in OCD patients may contribute to impaired neuronal integration and functionality.
Keywords: Obsessive -compulsive disorder; Oxidative stress; Neuronal integrity; Single proton magnetic resonance spectroscopy